Intervensi Youth Centered Web-Based for Depression (YOWES) Dalam Menurunkan Gejala Depresi Remaja - Itma Annah; Destonady Kadiser Miden; Irene Febriani (Madu Jurnal Ilmu Kebidanan, 2026)
Depression is one of the most common mental health problems among adolescents and can affect social, academic, and quality of life aspects. The high use of digital technology among adolescents has encouraged the development of web-based interventions as an alternative for mental health promotion. This study aimed to analyze the effect of the YOWES (Youth Centered Web-based for Depression) intervention on reducing depressive symptoms among adolescents in Palangka Raya City. This study used a one-group pretest-posttest experimental design without a control group. The sample consisted of 37 adolescents with severe depressive symptoms selected using purposive sampling. Depression was measured using the Children Depression Inventory (CDI) instrument. Data were analyzed using the Wilcoxon test. The results showed that most respondents were female (97.3%), aged 14–17 years (83.8%), and high school students (73.0%). There was a decrease in the mean depression score from 28.11 to 18.73 with a difference of 9.38 and a p-value of 0.000 (